Palm oil consumption and its repercussion on endogenous fatty acids distribution - Li, Rui Zhi; Chen Cao, .; Zheng, Zhao Jun; Yang, Xiao Yan; Tan, Chin Ping; Xu, Yong Jiang; Liu, Yuan Fa (Royal Society of Chemistry, 2021)
The consumption of saturated lipids in combination with a sedentary lifestyle increases the risk of obesity and metabolic syndrome. However, the distribution of endogenous fatty acids (FA) after the consumption of saturated lipids and the connection between FA distribution and lipid metabolism-related genes relative expression have not been fully elucidated to date. In this study, we characterized FA profiles in the liver and visceral fats of Sprague Dawley (SD) rats fed with a high-palm-oil diet. The investigation showed that the levels of C16:0 and C18:1 (n-9) increased significantly (P < 0.05) in the liver of the high-palm-oil group (POG), while C16:1 (n-7) and C18:2 (n-6) accumulated markedly (P < 0.05) in the visceral fats of the control group (CN). A correlation analysis indicated a negative correlation between C16:0 and C16:1 (n-7) in the epididymal fat of POG. Our study also demonstrated that the intake of saturated lipids caused changes in lipid metabolism-related gene expression, especially stearoyl-CoA desaturase (SCD), which was upregulated at the third week but was inhibited in the subsequent weeks in the POG liver and perirenal fat. The SCD had a notable positive correlation with C16:1 (n-7) in the POG liver and perirenal fat but a significant negative correlation with C16:0 in the POG epididymal fat. In conclusion, the results of this study indicate that a high-C16:0 diet may result in adaptive SCD expression, and these findings may help to elucidate the effects of dietary fat on lipid metabolism.